Nivel de salud mental en el personal de los establecimientos de salud de la región Loreto en el contexto COVID-19 año 2022-2023 - Camus Loayza, Yasser Yersin (2025)
Objectives: The aim is to describe the level of mental health among health facility staff in the Loreto region in the context of the 2022-2023 period of the pandemic. Methods: This cross-sectional descriptive study involved interviewing 264 healthcare workers from seven healthcare facilities with the highest caseload of patients with confirmed cases of SARS-CoV-2 in the first and second waves (2020 and 2021) in the years 2022 and 2023. Three disorders were assessed: anxiety, depression and stress (both work-related and traumatic). The following instruments were used: The Beck Anxiety Inventory (BAI I), the Beck Depression Inventory (BAI II), the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) and the Post Traumatic Stress Symptom Scale (PSS), respectively. There are very few studies in Peru about the level of mental health in healthcare workers during the pandemic. Results: The study shows 7.2% moderate anxiety and 24.6% depression (16.3% mild, 3.0% moderate and 5.3% severe). Regarding work-related stress, 28.8% presented a high level of emotional exhaustion, 18.9% a high level of depersonalization and 88.6% a low level of work efficiency. Traumatic stress was present in 26.1% (48.1% re-experiencing, 31.4% avoidance and 43.2% increased activation). Emotional exhaustion and the presence of post traumatic stress were significantly (P<0.05) associated with the presence of at least one comorbidity for COVID-19. Conclusions: Levels of anxiety, depression and stress were high in health personnel in the Loreto region where the highest COVID-19 cases were attended. Work-related stress and post-traumatic stress were the main disorders identified. It is recommended to inform, raise awareness and encourage policies for the promotion and prevention of mental health for health personnel working in health facilities in the Loreto region.